2014
DOI: 10.1371/journal.pone.0105316
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accuracy of Sentinel Lymph Node Biopsy in Clinically Node-Positive Breast Cancer after Neoadjuvant Chemotherapy: A Meta-Analysis

Abstract: Sentinel lymph node biopsy (SLNB) has replaced conventional axillary lymph node dissection (ALND) in axillary node-negative breast cancer patients. However, the use of SLNB remains controversial in patients after neoadjuvant chemotherapy (NAC). The aim of this review is to evaluate the feasibility and accuracy of SLNB after NAC in clinically node-positive patients. Systematic searches were performed in the PubMed, Embase, and Cochrane Library databases from 1993 to December 2013 for studies on node-positive br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 32 publications
4
45
0
4
Order By: Relevance
“…A multicenter prospective study from France reported a lower identification rate and higher false negative rate in clinical node-positive patients compared to node-negative disease at presentation [74]. Given the stark difference between these patient populations, two separate meta-analyses have been reported for cN0 [75] and cN1 [76] patients undergoing post-chemotherapy SLNB and axillary dissection. In 2011, the meta-analysis by Tan et al indicated that for clinically node negative patients, the false negative rate of 7% is similar to the false negative rate in patients without neoadjuvant chemotherapy [75].…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter prospective study from France reported a lower identification rate and higher false negative rate in clinical node-positive patients compared to node-negative disease at presentation [74]. Given the stark difference between these patient populations, two separate meta-analyses have been reported for cN0 [75] and cN1 [76] patients undergoing post-chemotherapy SLNB and axillary dissection. In 2011, the meta-analysis by Tan et al indicated that for clinically node negative patients, the false negative rate of 7% is similar to the false negative rate in patients without neoadjuvant chemotherapy [75].…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis has shown that post-NACT SLNB is associated with an acceptable pooled IR (89 %), but a poor FNR (14 %) [20]. This meta-analysis suggested that further studies be undertaken, especially in LABC patients, to identify factors associated with SLNB failure, with the intention of creating a well-defined 'selection criteria' for patients receiving NACT-aiming to achieve IR and FNR equivalent to that of SLNB in EBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first one involved 2471 patients and found an IR of 89% and an FNR of 14% [35]. According to the first study, usage of IHC decreased FNR to 8.7%, while without IHC, the FNR was 16%.…”
Section: Reviewmentioning
confidence: 99%